2014
DOI: 10.1371/journal.pone.0091647
|View full text |Cite
|
Sign up to set email alerts
|

Serum Thymidine Kinase Activity: Analytical Performance, Age-Related Reference Ranges and Validation in Chronic Lymphocytic Leukemia

Abstract: BackgroundTo date no age-related reference ranges are available for serum thymidine kinase (TK1) activity. Being a proliferation marker, it may be used as a prognostic marker in malignant diseases, including chronic lymphocytic leukemia (CLL). Our aim was to establish age-specific reference ranges for TK1 and examine its utility as a screening marker in CLL, a disease of the elderly.MethodsSerum TK1 activity was measured by a competitive chemiluminescent immunoassay in 369 healthy adults and 115 de novo CLL pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
5
1
Order By: Relevance
“…There was no significant difference in the median TK1 protein levels between three different age groups (young, middle-aged and older). These results are in contrast to those of a previously published study which found that TK1 enzyme activity in healthy individuals decreased significantly with age [21]. Furthermore, TK1 protein determinations using a dot blot assay have shown a similar pattern, with serum TK1 protein concentrations increasing up to the age of 40 years and then decreasing with age [22].…”
Section: Correlations With Other Blood Parameterscontrasting
confidence: 99%
“…There was no significant difference in the median TK1 protein levels between three different age groups (young, middle-aged and older). These results are in contrast to those of a previously published study which found that TK1 enzyme activity in healthy individuals decreased significantly with age [21]. Furthermore, TK1 protein determinations using a dot blot assay have shown a similar pattern, with serum TK1 protein concentrations increasing up to the age of 40 years and then decreasing with age [22].…”
Section: Correlations With Other Blood Parameterscontrasting
confidence: 99%
“…The standardization of chemiluminescence immunoassay for the assessment of serum thymidine kinase-1 (TK) levels significantly facilitated the introduction of this marker into clinical practice,100 and age-related normal reference values were recently defined and validated 101. When this test was included among diagnostic workup within prospective trials, raised TK levels (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Because of this characteristic, TK1 has been used as a proliferation marker in lymphomas and leukemias in human medicine for many years [1012]. Several commercial assays are available to measure the TK1 activity levels in different malignancies, such as e.g., TK-REA, TK-Liaison, and Divitum [10, 29, 30]. Even though TK1 activity levels show a correlation with the stage of breast cancer disease, the overall sensitivity of the assays is rather low i.e., less than 35 % [30–32].…”
Section: Discussionmentioning
confidence: 99%